2020
DOI: 10.1021/acsenergylett.0c00471
|View full text |Cite
|
Sign up to set email alerts
|

Nonradiative Energy Transfer between Thickness-Controlled Halide Perovskite Nanoplatelets

Abstract: Despite showing great promise for optoelectronics, the commercialization of halide perovskite nanostructure-based devices is hampered by inefficient electrical excitation and strong exciton binding energies. While transport of excitons in an energy-tailored system via Förster resonance energy transfer (FRET) could be an efficient alternative, halide ion migration makes the realization of cascaded structures difficult. Here, we show how these could be obtained by exploiting the pronounced quantum confinement ef… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
61
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(75 citation statements)
references
References 37 publications
11
61
2
Order By: Relevance
“…The energy band characteristics of both CsPBA-2 and SPR-001 were verified using ultraviolet photoelectron spectroscopy (UPS) which reveals the formation of a type I heterojunction (Figure 1c and Figure S1). This, coupled with the existence of a spectral overlap between the CsPBA-2 photoluminescence and SPR-001 absorbance spectra (Figure 1d), 16,31 supports the probability of non-radiative ET occurring, which further highlights the importance of spatial separation for effective white emission. The bilayered films are prepared by incorporating various concentrations of SPR-001 into the antisolvent and dripping it onto the sample midway during the spincoating of CsPBA-2 (Figure 2a).…”
mentioning
confidence: 60%
“…The energy band characteristics of both CsPBA-2 and SPR-001 were verified using ultraviolet photoelectron spectroscopy (UPS) which reveals the formation of a type I heterojunction (Figure 1c and Figure S1). This, coupled with the existence of a spectral overlap between the CsPBA-2 photoluminescence and SPR-001 absorbance spectra (Figure 1d), 16,31 supports the probability of non-radiative ET occurring, which further highlights the importance of spatial separation for effective white emission. The bilayered films are prepared by incorporating various concentrations of SPR-001 into the antisolvent and dripping it onto the sample midway during the spincoating of CsPBA-2 (Figure 2a).…”
mentioning
confidence: 60%
“…Indeed, the fluorescence average lifetime reduction of the blue emission at 478 nm from 0.66 ms of the NaYF 4 :30%Yb,0.5%Tm nanocrystals to 0.29 ms of the CsPbBr 3 –NaYF 4 :Yb,Tm nanocrystals (Supplementary Fig. 16 and Supplementary Table 5 ) suggested that the energy transfer from NaYF 4 :Yb,Tm to CsPbBr 3 in the heterostructure follows a typical FRET process 27 , 41 . The FRET efficiency can be calculated with the equation Eff = 1 − τ D–A /τ D , where Eff is the energy transfer efficiency, τ D–A is the effective lifetime of a donor conjugated with an acceptor, and τ D is the effective lifetime of a donor in the absence of an acceptor.…”
Section: Resultsmentioning
confidence: 99%
“…[33] Timeresolved fluorescence spectra of BP/CN in Figure 3b shows af aster radiation recombination to pristine CN nanosheet, representing the decreased lifetime of singlet excitons in BP/ CN. [1,34] As triplet excitons are derived from the intersystem crossing (ISC) progress of singlet excitons,low singlet exciton yield in the system directly leads to low triplet exciton concentration, and the reduction of triplet excitons will further reduce the probability of triplet-triplet annihilation (TTA) process. [35] In this case,t he BP/CN heterojunction exhibits weakened P-type delayed phosphorescence at low temperature (Figure 3c)w ith lifetime of about 1.48 ms (Figure 3d), lower than that of pristine CN (ca.…”
Section: Resultsmentioning
confidence: 99%
“…This couplings are crucial to the energy re‐balance mediated by both exciton‐based energy transfer and carrier‐based charge transfer in the system [33] . Time‐resolved fluorescence spectra of BP/CN in Figure 3 b shows a faster radiation recombination to pristine CN nanosheet, representing the decreased lifetime of singlet excitons in BP/CN [1, 34] . As triplet excitons are derived from the intersystem crossing (ISC) progress of singlet excitons, low singlet exciton yield in the system directly leads to low triplet exciton concentration, and the reduction of triplet excitons will further reduce the probability of triplet–triplet annihilation (TTA) process [35] .…”
Section: Resultsmentioning
confidence: 99%